2015
DOI: 10.1159/000380745
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Speech-in-Noise and Sound Localisation Abilities in Children with Unilateral Hearing Loss and Comparison to Normal Hearing Peers

Abstract: The study objective was to quantify abilities of children with unilateral hearing loss (UHL) on measures that address known deficits for this population, i.e. speech understanding in quiet and noise, and sound localisation. Noise conditions varied by noise type and source location. Parent reports of real-world abilities were also obtained. Performance was compared to gender- and age-matched normal hearing (NH) peers. UHL performance was poorer and more varied compared to NH peers. Among the findings, age corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
73
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 29 publications
10
73
0
6
Order By: Relevance
“…We know that informational masking is associated with an especially pronounced SRM in children with normal hearing (Johnstone & Litovsky 2006; Misurelli & Litovsky 2015), and initial data are consistent with the idea that UHL in children is particularly detrimental in speech-based maskers (Reeder et al, 2015). Further motivation for considering children’s performance in the presence of informational masking is based on recent data from Hillock-Dunn et al (2015).…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…We know that informational masking is associated with an especially pronounced SRM in children with normal hearing (Johnstone & Litovsky 2006; Misurelli & Litovsky 2015), and initial data are consistent with the idea that UHL in children is particularly detrimental in speech-based maskers (Reeder et al, 2015). Further motivation for considering children’s performance in the presence of informational masking is based on recent data from Hillock-Dunn et al (2015).…”
Section: Introductionsupporting
confidence: 63%
“…Based on the results of Reeder at al (2015), this association was predicted for attenuation at 500 Hz, but not at the other frequencies. Without correcting for multiple comparisons, the two-tailed bivariate correlation between children’s SRM and attenuation values at 500 Hz was statistically significant in the two-talker masker for the simUHL/msk-contra listening condition (r = −.609, p = .047), but not in the other masker conditions ( p ≥ .283).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Reeder et al reported that children with unilateral hearing loss have significant differences from their normal-hearing peers in terms of speech perception and localization [44]. Children with unilateral hearing loss have been shown to have worse language skills than their siblings with normal hearing [45].…”
Section: Treatmentmentioning
confidence: 99%